The urge for just transition: Evidence from understanding of wood fuel producers' livelihoods and vulnerability in the drylands of Ethiopia - Girma, Gonche; Shimeles, Abebaw; Abate, Tensaye; Seyoum, Gezahegn; Alemu, Mitiku (Frontiers in Sustainable Food Systems, 2022)
Wood fuel is not only the main source of energy for both rural and urban households but also a vital means of livelihood diversification for rural households to improve livelihood capital in developing countries like Ethiopia. However, the status of wood fuel producers' livelihood capital and their vulnerability is poorly understood in the drylands of Ethiopia. The main purpose of the research is to characterize the livelihoods of firewood and charcoal producers as well as identify sources of livelihoods' vulnerability in the dryland areas of the country. These urge to transit for sustainable energy use. The study used survey data collected from 857 sampled wood fuel producer households and Focus Group Discussions. The data were analyzed descriptively using livelihood measurement indicators and livelihood vulnerability indexes (exposure, sensitivity, and adaptive capacity indicators) in the context of farming, agro-pastoralist, and pastoralist communities. Results indicated that generally financial, human, and social capital of wood fuel producers were low whereas natural and physical capital were better. Results also indicated engagement in the production of wood fuel strengthened the producers' livelihood capital and delivered other benefits such as opportunities for livelihood diversification as well as reducing vulnerability and improved livelihoods. The pastoral and agro-pastoral communities' livelihood capital sources were more vulnerable than farming communities. The study has also identified that wood fuel production was one of the major coping strategies employed by the sampled households to mitigate the effects of different shocks. Finally, the study results implied that wood fuel production is the highest priority area of intervention to improve the livelihoods of communities in the dry lands. It is also worthwhile to establish sustainable approaches for wood fuel production keeping the dry land forest and environment safe. This calls policy for a just transition toward an equitable wood fuel production system with the potential to deliver sustainable energy and rural development through the incorporation of wood fuel importance to rural livelihoods.